Modeling Holistic Marks With Analytic Rubrics - Tomas, Carmen; Whitt, Emma; Lavelle-Hill, Rosa; Severn, Katie (Frontiers in Education, 2019)
Analytic and holistic marking are typically researched as opposites, generating a mixed and inconclusive evidence base. Holistic marking is low on content validity but efficient. Analytic approaches are praised for transparency and detailed feedback. Capturing complex criteria interactions, when deciding marks, is claimed to be better suited to holistic approaches whilst analytic rules are thought to be limited. Both guidance and evidence in this area remain limited to date. Drawing from the known complementary strengths of these approaches, a university department enhanced its customary holistic marking practices by introducing analytic rubrics for feedback and as ancillary during marking. The customary holistic approach to deciding marks was retained in the absence of a clear rationale from the literature. Exploring the relationship between the analytic criteria and holistic marks became the focus of an exploratory study during a trial year that would use two perspectives. Following guidance from the literature, practitioners formulated analytic rules drawing on their understanding of the role of criteria, to explain output marks by allocating weightings. Secondly, data derived throughout the year consisting of holistic marks and analytic judgements (criteria) was analysed using machine learning techniques (random forests). This study reports on data from essay-based questions (exams) for years 2 and 3 of study (n = 3,436). Random forests provided a ranking of the variable importance of criteria relative to holistic marks, which was used to create criterion weightings (data-derived). Moreover, illustrative decision trees provide insights into non-linear roles of criteria for different levels of achievement. Criterion weightings, expected by practitioners and data-derived (from holistic marks), reveal contrasts in the ranking of top criteria within and across years. Our exploratory study confirms that holistic and analytic approaches, combined, offer promising and productive ways forward both in research and practice to gain insight into the nature of overall marks and relations with criteria. Rather than opposites, these approaches offer complementary insights to help substantiate claims made in favour of holistic marking. Our findings show that analytic may offer insights into the extent to which holistic marking really aligns with assumptions made. Limitations and further investigations are discussed.